1973
DOI: 10.1177/000456327301000116
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a Simple Technique for the Determination of Serum Thyroxine

Abstract: The diagnostic accuracy and precision of the Thyopac-4 Kit for measuring serum thyroxine is described. A simple work-saving modification to the procedure is suggested and a normal range established. The test is satisfactory for the diagnosis of hypo-and hyperthyroidism, correlating well with clinical assessments and the measurement of T, uptake. The precision of the technique is considerably better than that for P.B.I. and there are no time or temperature dependent stages. It can be scaled down for paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1974
1974
1976
1976

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
1
4
1
Order By: Relevance
“…are similar to those of Badman and Platten (1973) who found a frequency of 10% contamination, and Watson and Lees (1973) who found a total of 22 % on the basis of known medication or (P.B.I.-T-4) greater than 4 I1g/100 ml. Lee et al (1972) found 'about a fourth' of specimens from 293 hospital patients to be contaminated, though not stating criteria for contamination.…”
Section: Discussionsupporting
confidence: 84%
“…are similar to those of Badman and Platten (1973) who found a frequency of 10% contamination, and Watson and Lees (1973) who found a total of 22 % on the basis of known medication or (P.B.I.-T-4) greater than 4 I1g/100 ml. Lee et al (1972) found 'about a fourth' of specimens from 293 hospital patients to be contaminated, though not stating criteria for contamination.…”
Section: Discussionsupporting
confidence: 84%
“…The semi-automated procedure also results in an improved precision over the manual method. Badman and Platten (1973), using a work simplified technique for Thyopac-4 estimations, also found an improved precision compared with the manual technique.…”
Section: Discussionmentioning
confidence: 82%
“…determinations as tests of thyroid function, but the former have the disadvantage of not being capable of automation. However, work simplification procedures for serum thyroxine determinations have recently been developed (Badman and Platten, 1973;Seth, 1973a), and the variables which affect the accuracy and precision of these procedures have been investigated (Seth, 1973b). This communication describes the adaptation of the Baird and Tatlock Analmatic preparation unit for the large scale estimations of serum thyroxine using Thyopac-4 kits (Radiochemical Centre, Amersham).…”
mentioning
confidence: 99%
“…9 11 There is not the same agreement at the upper limit. Badman and Platten (1973) and Watson and Lees (1973) have shown that the apparent value for serum thyroxine by CB.P. methods increased with storage at 4"C and 15-20 a C as compared with storage at -20 aC The formation of 'mimic T-4' might account in part for the higher upper limit of normal from laboratories using CB.P.…”
Section: Accuracy and Standardisation Of Serum Thyroxine Assaysmentioning
confidence: 99%